Application of personalized medicine to chronic disease: a feasibility assessment. Issue 1 (18th December 2013) - Dorfman, Ruslan; Khayat, Zayna; Sieminowski, Tammy; Golden, Brian; Lyons, Renee
Abstract: Personalized Medicine has the potential to improve health outcomes and reduce the cost of care; however its adoption has been slow in Canada. Bridgepoint Health is a complex continuous care provider striving to reduce the burden of polypharmacy in chronic patients. The main goal of the study was to explore the feasibility of utilizing personalized medicine in the treatment of chronic complex patients as a preliminary institutional health technology assessment. We analyzed stroke treatment optimization as a clinical indication that could serve as a "proof of concept" for the widespread implementation of pharmacogenetics. The objectives of the study were three‐fold: Review current practice in medication administration for stroke treatment at Bridgepoint Health Critically analyze evidence that pharmacogenetic testing could (or could not) enhance drug selection and treatment efficacy for stroke patients; Assess the cost‐benefit potential of a pharmacogenetic intervention for stroke. Review current practice in medication administration for stroke treatment at Bridgepoint Health Critically analyze evidence that pharmacogenetic testing could (or could not) enhance drug selection and treatment efficacy for stroke patients; Assess the cost‐benefit potential of a pharmacogenetic intervention for stroke. We conducted a review of stroke treatment practices at Bridgepoint Health, scanned the literature for drug‐gene and drug‐outcome interactions, and evaluated the potential consequences of pharmacogenetic testing using the ACCE model. There is a substantial body of evidence suggesting that pharmacogenetic stratification of stroke treatment can improve patient outcomes in the long‐term, and provide substantial efficiencies for the healthcare system in the short‐term. Specifically, pharmacogenetic stratification of antiplatelet and anticoagulant therapies for stroke patients may have a major impact on the risk of disease recurrence, and thus should be explored further for clinical application. Bridgepoint Health, and other healthcare institutions taking this path, should consider launching pilot projects to assess the practical impact of pharmacogenetics to optimize treatment for chronic continuous care.